Association between Knowledge and Vitamin D Serum Level among Vitamin D Consumers in Tehran, Iran - Ghader Mohammadnezhad; Maryam Talebi; Hadi Esmaily (International Journal of Nutrition Sciences, 2023)
Background: Results of studies in Iran indicated a high prevalence of vitamin D deficiency, making its rational use to be critical. So assessing people’s knowledge about the rational use of vitamin D and its safety is worthwhile to pursue. This study aimed to evaluate the level of consumers’ knowledge about vitamin D and its relationship with vitamin D serum levels in Tehran, Iran.Methods: A cross-sectional survey was designed to assess consumers’ knowledge and its association with demographic characteristics, lifestyle, habits and the serum 25-hydroxy vitamin D3 (25(OH)D) level in 10 community pharmacies in Tehran, Iran.Results: Totally, 384 individuals participated in this study, among whom 345 (89.8%) requested large doses of vitamin D. The average knowledge score was 23.67±7.76 out of 50. The average serum level of vitamin D was 49.01±32.01 ng/mL, showing that 117 (30.5%) subjects were in “insufficient”, 224 (58.1%) were in “sufficient”, and 44 (11.4%) were in “hypervitaminosis” levels. There was a significant inverse association between knowledge and age, weight, body mass index (BMI), educational level, vitamin D serum level, and monthly dose. Also, a significant inverse relationship was detected between knowledge in terms of toxicity and vitamin D level. Further, participants’ knowledge of “hypervitaminosis” was lower than those with “sufficient” level.Conclusion: More than 50% of consumers had a sufficient knowledge on vitamin D level, however the lack of knowledge about vitamin D was evident that could lead to misuse and hypervitaminosis, which were noticed in 11.4% of participants.